How do procurement and separation relate with performance management system among employees? testing the mediating role of Ict adoption - Nura, Abubakar Allumi; Osman, Nor Hasni (2013)
This study is aimed at revealing how performance management system (PMS) relates to procurement and separation among employees in an organization.Several researches have been embarked upon in determining how one or two human resource management (HRM) practice (s) influence employee performance, however, an approach to studying the mediating effect of ICT adoption between procurement and separation and performance management system is still begging for rigorous academic attention.To reduce this widely created gap, the paper aimed at determining whether the procurement and separation are correlated to performance management system.The results however obtained through SmartPLS confirmed that there is full mediation effect of ICT adoption on one relationship and a partial mediation effect on the other.